Non-pharmacological educational and self-management interventions for people with chronic headache: the CHESS research programme including a RCT - Underwood Martin; Achana Felix; Carnes Dawn; Eldridge Sandra; Ellard David R; Griffiths Frances; Haywood Kirstie; Hee Siew Wan; Higgins Helen; Mistry Dipesh; Mistry Hema; Newton Sian; et al. (NIHR Journals Library, 2023)
Background Headaches are a leading cause of years lived with disability. For some people, headaches become chronic and disabling, with treatment options being primarily pharmaceutical. Non-pharmacological alternative treatment approaches are worthy of exploration. Aim To develop and test an educational and supportive self-management intervention for people with chronic headaches. Objectives To develop and evaluate a brief diagnostic interview to support diagnosis for people with chronic headaches, and then to develop and pilot an education and self-management support intervention for the management of common chronic headache disorders (the CHESS intervention). To select the most appropriate outcome measures for a randomised controlled trial of the CHESS intervention, and then to conduct a randomised controlled trial and economic evaluation of the CHESS intervention with an embedded process evaluation. Design Developmental and feasibility studies followed by a randomised controlled trial. Setting General practice and community settings in the Midlands and London, UK. Participants For our feasibility work, 14 general practices recruited 131 people with chronic headaches (headaches on ≥15 days per month for >3 months). People with chronic headaches and expert clinicians developed a telephone classification interview for chronic headache that we validated with 107 feasibility study participants. We piloted the CHESS intervention with 13 participants and refined the content and structure based on their feedback. People with chronic headaches contributed to the decisions about our primary outcome and a core outcome set for chronic and episodic migraine. For the randomised controlled trial, we recruited adults with chronic migraine or chronic tension-type headache and episodic migraine, with or without medication overuse headache, from general practices and via self-referral. Our main analyses were on people with migraine. Interventions The CHESS intervention consisted of two 1-day group sessions focused on education and self-management to promote behaviour change and support learning strategies to manage chronic headaches. This was followed by a one-to-one nurse consultation and telephone support. The control intervention consisted of feedback from classification interviews, headache management leaflet and a relaxation compact disc. Main outcome measures The primary outcome was headache-related quality of life measured using the Headache Impact Test-6 at 12 months. The secondary outcomes included the Chronic Headache Quality of Life Questionnaire; headache days, duration and severity; EuroQol-5 Dimensions, five-level version; Short Form Questionnaire-12 items; Hospital Anxiety and Depression Scale; and Pain Self-Efficacy Questionnaire scores. We followed up participants at 4, 8 and 12 months. Results Between April 2017 and March 2019, we randomised 736 participants from 164 general practices. Nine participants (1%) had chronic tension-type headache only. Our main analyses were on the remaining 727 participants with migraine (376 in the intervention arm and 351 in the usual-care arm). Baseline characteristics were well matched. For the primary outcome we had analysable data from 579 participants (80%) at 12 months. There was no between-group difference in the Headache Impact Test-6 at 12 months, (adjusted mean difference -0.3, 95% confidence interval -1.23 to 0.67; p = 0.56). The limits of the 95% confidence interval effectively exclude the possibility of the intervention having a worthwhile benefit. At 4 months there was a difference favouring the CHESS self-management programme on the Headache Impact Test-6 (adjusted mean difference -1.0, 95% confidence interval -1.91 to -0.006; p = 0.049). However, the self-management group also reported 1.5 (95% confidence interval 0.48 to 2.56) more headache days in the previous 28 days. Apart from improved pain self-efficacy at 4 and 12 months, there were few other statistically significant between-group differences in the secondary outcomes. The CHESS intervention generated 0.031 (95% confidence interval -0.005 to 0.063) additional quality-adjusted life-years and increased NHS and Personal Social Services costs by £268 (95% confidence interval £176 to £377), on average, generating an incremental cost-effectiveness ratio of £8617 with an 83% chance of being cost-effective at a willingness-to-pay threshold of £20,000 per quality-adjusted life-year. The CHESS intervention was well received and fidelity was good. No process-related issues were identified that would explain why the intervention was ineffective. Limitations Only 288 out of 376 (77%) of those randomised to the CHESS intervention attended one or more of the intervention sessions. Conclusions This short, non-pharmacological, educational self-management intervention is unlikely to be effective for the treatment of people with chronic headaches and migraine. Future work There is a need to develop and test more sustained non-pharmacological interventions for people with chronic headache disorders. Patient and public involvement Substantial patient and public involvement went into the design, conduct and interpretation of the CHESS programme. This helped direct the research and ensured that the patient voice was embedded in our work. Trial registration This trial is registered as ISRCTN79708100. Funding This project was funded by the National Institute for Health and Care Research (NIHR) Programme Grants for Applied Research programme and will be published in full in Programme Grants for Applied Research; Vol. 11, No. 2. See the NIHR Journals Library website for further information. Plain language summary What did we want to find out? We wanted to find out if an education and self-management support programme for people with frequent headaches made these people feel better. What did we do? We first made sure that we could find people with frequent headaches, from general practice, who would want to take part in our study. We then trained nurses to do telephone interviews to find out what sort of headaches people had. We looked at previous research and then, together with people with frequent headaches, designed a group education and self-management programme. It was run by a nurse and another health professional over 2 days, followed by a one-to-one session and telephone support with a nurse. We worked with people with frequent headaches and health professionals specialising in headaches to agree how best to measure how headaches affect people's quality of life. We then tested our self-management programme. We recruited 736 people with frequent headaches, of whom 727 had migraine. Using a computer, we allocated them at random either to attend the self-management programme or to receive a relaxation compact disc. Everyone was told their headache type. We asked participants to tell us about their headaches and headache quality of life after 4 months, 8 months and 12 months. What did we find? Our main results are for the 727 people with migraine. Our support programme did not help people in our study with frequent migraines to live better. There were also no important differences in the number of headaches people had each month or the amount of prescribed or over-the-counter medication they took for their headaches. What does this mean? Our short 2-day programme did not appear to improve headache-related quality of life or reduce the number of headache days. Other ways of helping people manage their chronic headaches are needed. Scientific summary Background Headaches are second to low back pain as a global cause of years lived with disability. Headaches are the most common neurological disorder treated in primary care. They account for around 3% of general practitioner consultations. Seventy per cent of people with headaches seen by their general practitioner do not get a formal diagnosis. For some people headaches become a chronic disabling disorder. There is a need for more non-pharmacological treatments to help those living with headache disorders. Our overarching aim was to develop and test a supportive education and self-management group intervention, implementable in primary care, for people with chronic headaches.